2010
DOI: 10.1128/ec.00038-10
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Cyclin Clb4 Carries S-Phase Cyclin Activity

Abstract: Cyclin-dependent kinases (CDKs) are key regulators of eukaryotic cell cycle progression. The cyclin subunit activates the CDK and also imparts to the complex, at least in some cases, substrate specificity. Saccharomyces cerevisiae, an organism in which the roles of individual cyclins are best studied, contains nine cyclins (three G 1 cyclins and six B-type cyclins) capable of activating the main cell cycle CDK, Cdc28. Analysis of the genome of the pathogenic yeast Candida albicans revealed only two sequences c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
1
12
0
2
Order By: Relevance
“…Sol1 was identified as functional homolog of S. cerevisiae Sic1 in C. albicans . In C. albicans Sol1 may play a similar role to Sic1, as it has been reported that Sol1 inhibits CaClb4 and CaClb2 and that CaSol1 at high concentration is itself a substrate of both CaClb2 and CaClb4 (Ofir and Kornitzer, 2010). We show that Sol1 accumulates in the presence of oxidative challenge.…”
Section: Discussionmentioning
confidence: 94%
“…Sol1 was identified as functional homolog of S. cerevisiae Sic1 in C. albicans . In C. albicans Sol1 may play a similar role to Sic1, as it has been reported that Sol1 inhibits CaClb4 and CaClb2 and that CaSol1 at high concentration is itself a substrate of both CaClb2 and CaClb4 (Ofir and Kornitzer, 2010). We show that Sol1 accumulates in the presence of oxidative challenge.…”
Section: Discussionmentioning
confidence: 94%
“…However, the association of Gin4 with Clb2 was markedly stronger than with Clb4. This might be explained by the recent finding that Clb2 is the mitotic cyclin in C. albicans (Ofir and Kornitzer, 2010). By contrast, Gin4 association was barely detectable with either one of the two G1 cyclins Ccn1 and Cln3 (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Alternatively, no such homologue exists and C. albicans ensures the irreversibility of START by other means. Supporting the latter possibility is that no sequence homologues of the Cln1/2 cyclins can be detected in C. albicans besides Hgc1, which is not known to play a role in cell cycle progression (Zheng and Wang, 2004; Ofir and Kornitzer, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Schematic depiction of CaNrm1 localization and CaNrm1-CaSwi4/CaSwi6 interaction during the cell cycle and after exposure to hydroxyurea. detected in C. albicans besides Hgc1, which is not known to play a role in cell cycle progression (Zheng and Wang, 2004;Ofir and Kornitzer, 2010).…”
Section: Cell Cycle Regulation Of Canrm1mentioning
confidence: 99%